Assessing the Seamlessness of Bangkok Metropolitan Public Transport by using Modified Quantitative Gap Analysis (International Journal of Built Environment and Sustainability, 2019)
A sustainable transportation system requires a larger contribution to public transport share in comparison to private transport. Bangkok Metropolitan, the study area, exhibits a significant transport modal alteration trend towards public transport, in line with the expansion of Bangkok Transit System (BTS) and Mass Rapid Transit (MRT) for more coverage within the metropolis along main roads along with expansion of public bus routes, which increases the seamlessness and reduces transit time. This study is important as we believe that the higher seamlessness the more urban travelers would shift to using public transport modes. This matter is considered as a pertinent urban transport problem. This study aims at understanding the level of transit seamlessness of the Bangkok public transport system.  The study was carried out by firstly measuring six factors of the regular transit process, on formal and informal transport modes used by Bangkokians. These six factors were observed along the origin and the destination of the travelers with respect to travel time, number of transit points, average transit time, comfort, and transit facilities including facilities for disables, and walking distance. A total number of 300 public transport users were selected as respondents, 50 respondents for each selected transit hub. The selection was based on convenient random sampling considering the variability of destinations and purpose of travel. Despite a different destination, the residence was set as the origin. By using Modified Quantitative Gap Analysis, based on six selected transit hubs, the study found that the seamlessness of the inter-modal transits in Bangkok exhibits a characteristics of hard transit process, particularly for disabled people, notwithstanding the continuous efforts to make the seamless transit are in place, particularly with respect to infrastructure facilities.
Keywords: Public transport; transit system; seamless transit; formal transport; informal transport modes.